Frequency and Severity of COPD in Smokers - SYED MAZHAR ALI NAQVI FAISAL HASSAN CH, NOOR-UL-ARFEE (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency and severity of COPD in smokers working at Services Hospital/SIMS, Lahore by using spirometry. Study design: Cross-sectional survey. Subjects & methodology: This study was conducted at Department of Pulmonology, Services Hospital, Lahore from July 2010 to February 2011. Total 100 cases (Doctors/paramedical staff working in Services Hospital, Lahore were included in this study. Patients were labeled as having COPD if FEV1 /FVC <0.70. Severity of COPD, the classification cutoffs were mild (FEV1 >80%), moderate (FEV1 80-50%), severe (FEV1 50-30%), very severe (FEV1<30%), and ratio of FEV1/FVC, < 0.70 in all the cases. Results: Number of pack years 5-30 were most common (Table-3). COPD was developed in 42 patients (42.0%). Out of these 42, severity of chronic obstructive pulmonary disease (COPD) as follows: mild 20 (47.7%), moderate 14 (33.3%), severe 7 (16.7%) and very severe 1 (2.3%). Out of these 42 patients with COPD, 39 (92.8%) were males and 3 (7.2%) were females. Conclusion: The higher prevalence of COPD in smokers clearly showed the effectiveness and a rationale to conduct screening in the most target group (smokers).